Fasting plasma glucose variability levels and risk of adverse outcomes among patients with type 2 diabetes: A systematic review and meta-analysis. (February 2019) - Zhao, Qian; Zhou, Fan; Zhang, Yusheng; Zhou, Xiaoyan; Ying, Changjiang
Highlights: For median or mean FPG variability under 20%, the relationship between all-cause mortality and FPG variability was not significant. High FPG variability was positively associated with the risk of retinopathy in patients with type 2 diabetes. FPG variability was positively associated with the risk of all-cause mortality in patients with type 2 diabetes. Abstract: Aim: This systematic review and meta-analysis assessed the association between fasting plasma glucose (FPG) variability levels and the risk of retinopathy and all-cause mortality in patients with type 2 diabetes. Methods: PubMed and EMBASE were searched to identify studies that evaluated the association between FPG variability and retinopathy and all-cause mortality in patients with type 2 diabetes mellitus. The hazard ratios (HRs) and 95% confidence intervals (CIs) were pooled with the random-effects model. Results: Eight studies were included in our meta-analysis. Five studies evaluated the impact of FPG variability on all-cause mortality and showed that high FPG variability was associated with the risk of all-cause mortality (HR 1.28, 95% CI 1.12–1.46; three studies). For median or mean FPG variability levels under 20%, the relationship between all-cause mortality and FPG variability was not significant. Three studies evaluated FPG variability and the risk of diabetic retinopathy and showed that high FPG variability was strongly associated with the risk of retinopathy (odds ratio (OR) = 3.68; 95% CI 1.01–13.4). Conclusion: High FPG variability levels were positively associated with the risk of retinopathy and all-cause mortality in patients with type 2 diabetes.